1999
DOI: 10.1073/pnas.96.4.1246
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of intact and N-terminal fragments of the human prolactin/growth hormone family members on angiogenesis: An efficient mechanism for the regulation of angiogenesis

Abstract: Angiogenesis, the process of development of a new microvasculature, is regulated by a balance of positive and negative factors. We show both in vivo and in vitro that the members of the human prolactin͞growth hormone family, i.e., human prolactin, human growth hormone, human placental lactogen, and human growth hormone variant are angiogenic whereas their respective 16-kDa N-terminal fragments are antiangiogenic. The opposite actions are regulated in part via activation or inhibition of mitogen-activated prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
213
2
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(229 citation statements)
references
References 46 publications
8
213
2
6
Order By: Relevance
“…In addition, expression of the prolactin gene is detected in capillary endothelial cells, and prolactin acts in an autocrine−paracrine fashion to regulate cellular proliferation (Clapp et al, 1998). The opposite actions of the intact and 16 kDa cleaved fragment are mediated by independent receptors rather than by competition for binding to the same receptor (Struman et al, 1999). Ligand binding and chemical crosslinking studies confirm that the 16 kDa prolactin fragment but not the 23 kDa prolactin binds to high affinity saturable sites in endothelial cell membranes, which are distinct in size from the cloned prolactin receptors (Clapp and Weiner, 1992).…”
Section: Angiogenesismentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, expression of the prolactin gene is detected in capillary endothelial cells, and prolactin acts in an autocrine−paracrine fashion to regulate cellular proliferation (Clapp et al, 1998). The opposite actions of the intact and 16 kDa cleaved fragment are mediated by independent receptors rather than by competition for binding to the same receptor (Struman et al, 1999). Ligand binding and chemical crosslinking studies confirm that the 16 kDa prolactin fragment but not the 23 kDa prolactin binds to high affinity saturable sites in endothelial cell membranes, which are distinct in size from the cloned prolactin receptors (Clapp and Weiner, 1992).…”
Section: Angiogenesismentioning
confidence: 68%
“…Prolactin stimulates and inhibits angiogenesis: the intact prolactin molecule is angiogenic and its N-terminal 16 kDa fragment is anti-angiogenic (Struman et al, 1999). In addition, expression of the prolactin gene is detected in capillary endothelial cells, and prolactin acts in an autocrine−paracrine fashion to regulate cellular proliferation (Clapp et al, 1998).…”
Section: Angiogenesismentioning
confidence: 99%
“…We also demonstrated that synthesis of a 16-kDa prolactin slightly increased in SS patients. 16-kDa prolactin is the result of the enzymatic cleavage of 22-kDa prolactin (Mittra, 1980), and it has recently been found that the 16-kDa compound has an antiangiogenic effect (Struman et al, 1999). The presence of PRL receptors was shown in striated duct cells using either anti-PRL-receptor or anti-S100A6 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit polyclonal antibodies were obtained (Eurogentec, Seraing, Belgium) using bacterially expressed and purified hPRL 16 kDa fragment (Struman et al, 1999) and shown to recognize the 23 kDa hPRL. These and monoclonal anti-phospho-JNK (Santa Cruz Biotechnology, Santa Cruz, CA) were used for immunofluorescence staining analysis.…”
Section: Reagentsmentioning
confidence: 99%